Toward a better definition of EPCAM deletions in Lynch Syndrome: Report of new variants in Italy and the associated molecular phenotype. Issue 5 (27th March 2019) - Cini, Giulia; Quaia, Michele; Canzonieri, Vincenzo; Fornasarig, Mara; Maestro, Roberta; Morabito, Alberto; D'Elia, Angela Valentina; Urso, Emanuele Damiano; Mammi, Isabella; Viel, Alessandra
Abstract: Background: Inherited epimutations of Mismatch Repair (MMR) genes are responsible for Lynch Syndrome (LS) in a small, but well defined, subset of patients. Methylation of the MSH2 promoter consequent to the deletion of the upstream EPCAM gene is found in about 1%–3% of the LS patients and represents a classical secondary, constitutional and tissue‐specific epimutation. Several different EPCAM deletions have been reported worldwide, for the most part representing private variants caused by an Alu ‐mediated recombination. Methods: 712 patients with suspected LS were tested for MMR mutation in our Institute. EPCAM deletions were detected by multiplex ligation‐dependent probe amplification (MLPA) and then defined by Long‐Range polymerase chain reaction (PCR)/Sanger sequencing. A comprehensive molecular characterization of colorectal cancer (CRC) tissues was carried out by immunohistochemistry of MMR proteins, Microsatellite Instability (MSI) assay, methylation specific MLPA and transcript analyses. In addition, somatic deletions and/or variants were investigated by MLPA and next generation sequencing (NGS). Results: An EPCAM deletion was found in five unrelated probands in Italy: variants c.556‐490_*8438del and c.858+1193_*5826del are novel; c.859‐1430_*2033del and c.859‐670_*530del were previously reported. All probands were affected by CRC at young age; tumors showed MSI and abnormal MSH2/MSH6 proteins expression. MSH2 promoter methylation, as well as aberrant in‐frame or out‐of‐frame EPCAM/MSH2 fusion transcripts, were detected in CRCs and normal mucosae. Conclusion: An EPCAM deletion was the causative variant in about 2% of our institutional series of 224 LS patients, consistent with previously estimated frequencies. Early age and multiple CRCs was the main clinical feature of this subset of patients. Abstract : EPCAM deletions were found in five families with Lynch Syndrome (2% of cases). A comprehensive molecular characterization of tumors showed microsatellite instability, abnormal MSH2/MSH6 proteins expression, MSH2 promoter methylation, as well as aberrant in‐frame or out‐of‐frame EPCAM/MSH2 fusion transcripts. Early age and multiple CRCs was the main clinical feature of this subset of patients.